Antimicrobial peptides and pro‐inflammatory cytokines are differentially regulated across epidermal layers following bacterial stimuli. Issue 12 (December 2013) - Percoco, Giuseppe; Merle, Chloé; Jaouen, Thomas; Ramdani, Yasmina; Bénard, Magalie; Hillion, Mélanie; Mijouin, Lily; Lati, Elian; Feuilloley, Marc; Lefeuvre, Luc; Driouich, Azeddine; Follet‐Gueye, Marie‐Laure
Abstract The skin is a natural barrier between the body and the environment and is colonised by a large number of microorganisms. Here, we report a complete analysis of the response of human skin explants to microbial stimuli. Using this ex vivo model, we analysed at both the gene and protein level the response of epidermal cells to Staphylococcus epidermidis (S. epidermidis) and Pseudomonas fluorescens (P. fluorescens), which are present in the cutaneous microbiota. We showed that both bacterial species affect the structure of skin explants without penetrating the living epidermis. We showed by real‐time quantitative polymerase chain reaction (qPCR) that S. epidermidis and P. fluorescens increased the levels of transcripts that encode antimicrobial peptides (AMPs), including human β defensin (hBD)2 and hBD3, and the pro‐inflammatory cytokines interleukin (IL)‐1α and (IL)‐1‐β, as well as IL‐6. In addition, we analysed the effects of bacterial stimuli on the expression profiles of genes related to innate immunity and the inflammatory response across the epidermal layers, using laser capture microdissection (LCM) coupled to qPCR. We showed that AMP transcripts were principally upregulated in suprabasal keratinocytes. Conversely, the expression of pro‐inflammatory cytokines was upregulated in the lower epidermis. These findings were confirmed by protein localisation using specific antibodies coupled to optical or electron microscopy. This work underscores the potential value of further studies that use LCM on human skin explants model to study the roles and effects of the epidermal microbiota on human skin physiology.